Legal Protection for Banking Institutions in Small and Medium Enterprise Credit Agreements - Sirait, Regina Ulianna; Sudirman, Lu; Disemadi, Hari Sutra (SIGn Jurnal Hukum, 2024)
Legal protection for banking institutions in Small and Medium Enterprise (SME) Credit Agreements is a fundamental issue in maintaining the financial system’s stability and promoting economic growth. This research analyzes the legal framework and legal certainty of protection for banks in SME Credit Agreements in Indonesia. This normative legal research uses a statute approach, with primary data sources in the form of relevant legislation and secondary data sources in business law literature. The results show that the juridical basis of protection for banks consists of preventive regulations (prudential principles, credit agreements, collateral, FSA supervision) and repressive regulations (credit restructuring, collateral execution, dispute resolution). Although this legal framework is comprehensive, its implementation faces significant challenges, such as inconsistent law enforcement, legal loopholes in collateral regulations, and the complexity of the judicial process. To improve legal certainty, regulatory reform, capacity building of law enforcement officials, information technology adoption, and supervision strengthening are recommended. Thus, this research contributes to strengthening legal protection for banking institutions, which will support the creation of a healthy and sustainable credit ecosystem for SMEs.